A Forma da Outra Arquitetura Orgânica - Milène Borges Masson (2023)
The works of architect Álvaro Siza were seen as examples to follow, right from my first year of college. Prior to this study, in which I deepened this issue of Organic architecture, I identified in Siza's work, almost by instinct, examples of works that seem to have the same concerns that Organic architecture encompasses. I do not consider Organic architecture as an architectural Movement or Style, for the simple fact that Organic architecture is, for me, a design strategy. So much so that it manages to share characteristics of other architectures. First of all, it became important to understand the concept of Organicity and what makes a work be considered Organic. For this, it is essential to study its contextualization. Predecessor Architectural Movements or Styles are analysed, with the aim of comparing them with Organicity. Only after this contextualization is it possible to study and understand the architecture of Frank Lloyd Wright and other architects who are associated with Organic architecture. The definition of Organic architecture does not arise a priori from the analysis of Siza's works, but rather during their research. Despite presenting my dissertation in two parts, it does not mean that its development has arisen in this way. The first part is an attempt at a deeper understanding of Organicity based on constellations of architectural works. That is, I identified other architects who also had the same problems and who worked with the same principles of Organic architecture. The second part of the work tries to develop in time and space an idea once pointed out by Kenneth Frampton. In the book "Álvaro Siza: Complete Works", Frampton determines a period in the work of Álvaro Siza, which he identifies as associated with Organic architecture. This analysis by Frampton on Siza's work thus becomes my anchor in the development of this dissertation, as it helped me to understand the definition of Organic architecture. However, in my understanding, this design strategy is not limited to a specific period, but is more transversal to the architect's work. Therefore, as a work strategy, I was interested in seeing a previous work and a later work by the architect Álvaro Siza. These analyzes of works more distant in time, compared to the period identified by Kenneth Frampton, arise with the aim of demonstrating my conviction that Organicity expanded over a longer period of time in Siza's work. Within the chapter by Álvaro Siza (Part 2), we find the following subchapters: - Piscina de Marés - work prior to the period identified by Kenneth Frampton. - Siza "Towards an Organic Architecture: 1969-1982" - study of works from this period. - House in Mallorca - a more recent work, with the aim of making a bridge to the architecture recently designed by Álvaro Siza. Within each case study, a comparison is made with other works, both by the same architect and others, to better understand the Organic characteristics in Siza's architecture. When studying the works of the architect Álvaro Siza in terms of this theme, it was not intended to make a complete study of all the details that the works contain. Organic architecture is often linked to formal issues, when it goes beyond form. Alvar Aalto says: "(...) But I would like to add, from a personal, emotional point of view, that architecture and its details are, in a way, biology. Perhaps they resemble a large salmon or a trout. They are not born adults, nor are they born in the sea or water where they normally live. They are born hundreds of miles from their habitat, where the rivers are reduced to small streams, clear streams between the falls, under the first drops of water from the melting ice, as remote from their usual life as human emotion and instinct are from the work of every day". This comparison is made in relation to the creative process of project development. But the form of architecture can also be seen as an organism. Where it needs parts for the proper functioning of the form, and that the parts constitute equivalent to a whole. But above all, form follows function, where only constraints shape the form of the project.